Antioxidant Activities, Phenolic Contents and Electronic Nose Analysis of Black Garlic - Ozan Emre Eyupoglu (International Journal of Secondary Metabolite)
Black garlic is a processed garlic product with a moisture-controlled high temperature heat treatment for a long time. In order to determine the secondary metabolites of black garlics treated in the study, firstly, in vitro antioxidant activities of black garlics purchased from Edovital company, Kastamonu, Turkey were determined, followed by qualitative and quantitative measurement of the phenolic compound content by HPLC and finally the electronic nose analysis of the content of nebulizer vapors in wood vinegar extract of black garlics were done successfully. Chlorogenic acid, vanillic acid, benzoic acid, gallic acid contents in detected 13 phenolic acids were quitely high. All quantitative results were expressed as mg gallic acid equivalent (GAE) per g dry matter of black garlic sample. ABTS and DPPH antioxidant activities were very low according to BHT standart and 2-Methylene-4-pentenal (18%) and Furfural (25%) were detected in high amount with electronic nose in nebulvapor contents of black garlic wood vinegar extract.